2019
DOI: 10.1016/j.apsusc.2019.03.168
|View full text |Cite
|
Sign up to set email alerts
|

On a specific state of C60 fullerene in N-methyl-2-pyrrolidone solution: Mass spectrometric study

Abstract: A solution of fullerene C 60 in N-methylpyrrolidone (NMP) presents a suitable system for tunable size. However, a mechanism of interaction of a polar NMP solvent with the fullerene molecules is still elusive. Herein, we present the laser desorption/ionization mass spectra (LDI MS) of the precipitates produced from C 60 /NMP solutions of different age in comparison with the typical spectra of C 60 crystallized from toluene and benzene. The distinctive characteristics of the C 60 /NMP mass spectra were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 68 publications
1
28
0
2
Order By: Relevance
“…Besides the time-dependent solvatochromic effect, the studies of the C 60 /NMP/water and C 70 /NMP/toluene systems [54,55] also revealed the drastic appearance of the solvatochromism when adding second solvent to the initial C 60 /NMP system, the absorption spectrum of which had not been ultimately smoothed out yet [56]. It was shown that the both effects emerge owing to the formation of donor-acceptor bonds [50,57], which, according to the results of theoretical calculations, are formed between oxygen atoms in the NMP molecule and carbon atoms of fullerene [58,59]. The formation of donor-acceptor bonds is responsible for the aggregate stabilization and changes the fullerene properties.…”
Section: Properties Of Fullerene Solutions In the Mixtures Of Organicmentioning
confidence: 95%
“…Besides the time-dependent solvatochromic effect, the studies of the C 60 /NMP/water and C 70 /NMP/toluene systems [54,55] also revealed the drastic appearance of the solvatochromism when adding second solvent to the initial C 60 /NMP system, the absorption spectrum of which had not been ultimately smoothed out yet [56]. It was shown that the both effects emerge owing to the formation of donor-acceptor bonds [50,57], which, according to the results of theoretical calculations, are formed between oxygen atoms in the NMP molecule and carbon atoms of fullerene [58,59]. The formation of donor-acceptor bonds is responsible for the aggregate stabilization and changes the fullerene properties.…”
Section: Properties Of Fullerene Solutions In the Mixtures Of Organicmentioning
confidence: 95%
“…Unfortunately, in reports providing the values of solubility there are not sufficient information about solid phase present in the equilibrium with the saturated solutions. Although no direct clues about C60 solvates can be inferred from solubility measurements this aspect was not overlooked and attracted serious attention by many investigators [10][11][12][13][14][15][16][17][64][65][66][67][68]. For example, the dissolution properties of C60 in aromatic solvents were studied using the thermos-analytical approach [10,12] and many solid solvates were identified.…”
Section: Computations Of C60 Fusion From Solubility Measurementsmentioning
confidence: 99%
“…It is also worth mentioning that the reference solvent method cannot help in the cases if solid states in equilibrium with saturated solutions comprise solvates. Since, there is a vast gross of evidences [10][11][12][13][14]16,17,[64][65][66]68] that Buckminster can interact with many solvents, it is quite clear that reference solubility cannot be used neither for serious improvement of predicted solubility data nor for treating cases of unknown fusion characteristics.…”
Section: Reference Solvent Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the effect of solvent polarity (using binary mixtures) reveals a certain transitional value of the dielectric permittivity of a solvent [26]. A subclass of these systems can be distinguished for the nitrogen-containing solvents such as N-methyl-pyrrolidone (NMP) [27][28][29][30] and pyridine [8]. The formation of donor-acceptor type complexes between fullerene and solvent molecules takes place [30][31][32], and a peculiar transition from a molecular to a stable colloidal solution, accompanied by the color change, can be observed.…”
Section: Introductionmentioning
confidence: 99%